INSIDER OWNERSHIP, DIVIDEN, DAN KEBIJAKAN HUTANG: PERAN MODERASI FREE CASH FLOW - Ariyanti, Prita Sukma (Jurnal Riset Akuntansi dan Keuangan, 2013)
The purpose of this study is to examine the moderating role of free cash flow to relationship between insider ownership and dividend toward debt policy. This studi uses non-banking and insurance firms, which listed in the indonesian stock market over 2004 - 2008. Empirical data are analyzed by using pooled least square method. The results show that insider ownership has positive influence on debt policy meanwhile dividend payout ratio has negative influence on debt policy. Free cash flow has the moderating effect on the relationship between insider ownership and dividend toward debt policy. Keywords: Insider Ownership, Dividend Payout Ratio, Debt Policy, Free Cash Flow.